Physical and Psychological Factors Associated with Non-specific Low Back Pain among Female Cleaners in Academic Settings - Chaichan, Kristsada; Pensri, Praneet (Journal of Health Science and Alternative Medicine, 2023)
Introduction: Low back pain (LBP) is the most common musculoskeletal disorder (MSD). Cleaning professions are strenuous and physically demanding jobs that often require cleaners to perform awkward movements during cleaning tasks. Although several studies have reported a high prevalence of LBP in cleaners, few studies have identified the physical and psychological factors associated with non-specific LBP (NSLBP) in this population. The study aimed to determine the associations between physical and psychological variables and the presence of NSLBP in female cleaners working in an academic setting. Methods: One hundred and ninety-nine female cleaners aged 18 to 60 years old with and without LBP were asked to complete a set of self-reported questionnaires to determine individual and work-related variables and quality of life and a Nordic body map to identify NSLBP. Binomial logistic regression analyses were used to determine associations between physical and psychological factors and the presence or absence of NSLBP. Results: The overall prevalence of MSDs among cleaners was 66.92% in the last 3 months and 43.23% time at present. NSLBP accounted for the majority of MSDs, with a prevalence of 30.24% in the last 3 months and 18.08% time at present. There was a significant association between NSLBP and the WHOQOL physical health domain (AOR= 0.78; 95% CI= 0.69–0.88), the frequency of bending forward during work (AOR= 0.33; 95% CI= 0.13–0.81), the frequency of squatting or kneeling during work (AOR=3.29; 95% CI= 1.06–10.19), feeling exhausted after work (AOR= 4.51; 95% CI= 1.03–19.69), and job dissatisfaction (AOR=0.64; 95%CI= 0.01–0.22). Conclusion: NSLBP was the most commonly reported work-related MSD among cleaners in an academic setting. Physical factors, including good or bad working postures, and psychological factors, including mental exhaustion, were significantly associated with the existence of NSLBP in cleaners.